Mononeuropathy of the suprascapular nerve: Study of 3 South American cases - Kashiwagi, F. T. [UNESP]; Resende, Luan A.L. [UNESP]; Bertotti, M. F Z [UNESP]; Souza, M. T M [UNESP]; Fonseca, Ronaldo Guimarães [UNESP] (My University, 2005)
In this work 3 new cases of suprascapular nerve mononeuropathy are described. ENMG diagnosis criteria were: a) normal sensory conduction studies of the ipsolateral ulnar, median and radial nerves; b) bilateral suprascapular nerve latencies with bilateral compound muscle action potential, obtained from the infraspinatus muscle with symmetrical techniques; and c) abnormal neurogenic infraspinatus muscle electromyographic findings, coexisting with normal electromyographical data of the ipsolateral deltoideus and supraspinatus muscles. These 3 cases of suprascapular mononeurpathy were found in 6,080 ENMG exams from our University Hospital. For us this mononeuropathy is rare with a 0.05% occurrence.
Keywords: Mononeuropathy; Suprascapular nerve; antiinflammatory agent; nonsteroid antiinflammatory agent; adult; case report; deltoid muscle; electromyography; human; male; median nerve; mononeuropathy; muscle action potential; patient attitude; radial nerve; rare disease; scapula; sensory nerve conduction; shoulder pain; South America; treatment indication; treatment refusal; ulnar nerve; Adult; Aged; Brazil; Electromyography; Humans; Male; Middle Aged; Mononeuropathies; Muscle, Skeletal; Muscular Atrophy; Neural Conduction; Scapula